Implementasi Rekrutmen Sumber Daya Manusia di Madrasah Aliyah Negeri 2 Sumedang - Ari Prayoga; Arif Risnandi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2019)
The public relations field at Madrasah Aliyah Negeri 2 Sumedang is less informative when carrying out open employee recruitment so that job seekers are less aware of recruitment information. This study aims to reveal the implementation of human resource recruitment at Madrasah Aliyah Negeri 2 Sumedang. The research method used is qualitative. The technique of collecting data uses interviews, observation and documentation studies. The results of the study show that First, the recruitment tool at the Madrasah Aliyah Negeri 2 Sumedang uses social media advertising media using online pamphlets. The media forum was informed, namely universities to target fresh graduates. Second, organizational characteristics in madrasas that are very thick with Islamic religious nuances are very good at attracting applicants from Islamic tertiary institutions, the achievements of institutions with well-managed management of madrasas are one of the attractions for job applicants. Third, minimal compensation or salary policies make recruitment difficult. Very strict job requirements in administration in state-run madrasa aliyah with long procedures make it one of the obstacles to complaints from prospective employees.